Experimental assessment of time-reversed OFDM underwater communications - Gomes, J. (2014)
OFDM communication has recently been demonstrated in underwater channels at rates of 10-30 kbps. This is a popular modulation in radio communications due to its spectral exibility and the simplicity of FFT-based transmitters/receivers. Despite widespread interest, experimental data on the performance of underwater OFDM are still scarce. This work aims to contribute to a better understanding of the potential of this technique by examining results from the UAB'07 experiment, which was conducted in Norway, in September 2007. Modulated data were transmitted in a fjord using several formats with bandwidths of 1.5 and 4.5 kHz, and recorded at a range of about 800 m in a 16-hydrophone array. Signi cant multipath was observed over a period of at least 30 ms, which would call for a large OFDM pre x and hence drastically reduce the data rate. Passive time reversal is used here as a computationally inexpensive preprocessing scheme to shorten the e ective channel length to less than 10 ms, so that moderate guard intervals can be used with a conventional OFDM receiver architecture. The same marker signals used for packet synchronization and Doppler compensation are reused as channel probes for passive time reversal, so the latter entails no loss in e ciency.